Ammonia reforming catalyst, method for producing ammonia reforming catalyst, and method for producing hydrogen gas

By using copper-iron composite oxide as ammonia hydrogen reduction catalyst, the problems of limited reserves of precious metals and low hydrogen generation efficiency are solved, and efficient and stable hydrogen generation is achieved, which is suitable for large-scale commercial applications.

JP2025037741APending Publication Date: 2025-03-18ACR CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023144862
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-06
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

In existing ammonia hydrogen reduction catalysts, precious metals such as erbium and erbium compounds are used with limited reserves, and the hydrogen generation efficiency in ammonia oxidation reaction is low, which cannot meet the needs of large-scale commercial applications.

Method used

Copper-iron composite oxides, especially copper ganglite type CuFe2O4 and copper Dravetseid type CuFeO2, are used as catalysts, and coexist with copper oxygen CuO(II) to improve catalytic activity and high temperature stability.

Benefits of technology

It achieves efficient and direct decomposition of ammonia to generate hydrogen, improves hydrogen generation efficiency and concentration, and maintains catalytic activity under high temperature conditions. It is suitable for fuel cells and hydrogen internal combustion engines and other applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025037741000001_ABST
    Figure 2025037741000001_ABST
Patent Text Reader

Abstract

To provide an ammonia reforming catalyst that supplies hydrogen with high hydrogen generation efficiency and possesses high-temperature durability suitable for use in SOFC fuel cells and hydrogen internal combustion engines, where the catalyst comprises a mixture of CuO and a copper spinel-type CuFe2O4 and / or copper delafossite-type CuFeO2 complex oxide.SOLUTION: An ammonia reforming catalyst for generating hydrogen gas from ammonia gas contains a copper spinel-type CuFe2O4 and / or copper delafossite-type CuFeO2 complex oxide.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an ammonia reforming catalyst that generates hydrogen from oxygen-free ammonia gas, and the ammonia reforming catalyst is a composite oxide made of copper and iron, which are base metals used in various materials, and includes a composite oxide having a crystal structure of copper spinel type CuFe2O4 and / or copper delafossite type CuFeO2, and further contains copper oxide (II). The present invention also relates to a method for producing the ammonia reforming catalyst and a method for producing hydrogen gas. [Background technology]

[0002] At present, there is a need to move to a hydrogen society as a measure against global warming and to protect the environment. Ammonia, which does not contain carbon, a source of CO2, is a stable energy source and is therefore highly anticipated not only as a direct fuel for engines, but also as a hydrogen carrier due to its high hydrogen content (17.8% by mass) and the fact that it can be easily liquefied under pressure at room temperature. It can also be used as fuel for hydrogen engines and fuel cells by gasifying liquefied ammonia at 30-100°C and extracting hydrogen from the ammonia.

[0003] In order to utilize ammonia in the above-mentioned various applications, it is necessary to generate a hydrogen-containing gas by decomposing vaporized ammonia gas efficiently at low temperatures using a catalyst as a method for extracting hydrogen from ammonia. As such a catalyst, noble metal catalysts in which noble metals such as ruthenium or rhodium are supported on various metal oxides have been known (Patent Documents 1 to 4).

[0004] Patent Document 1 discloses an ammonia reforming catalyst containing ruthenium that obtains hydrogen through an endothermic reaction shown in Formula 1 that directly decomposes ammonia.

[0005] 2NH3→ N2+ 3H2 (Formula 1)

[0006] On the other hand, Patent Documents 2 to 4 disclose an ammonia reforming catalyst containing ruthenium and rhodium as a catalyst for a method of producing hydrogen by mixing oxygen with ammonia at a low temperature when starting a hydrogen engine or fuel cell, as shown in Formula 2, and utilizing the heat generated by the ammonia oxidation reaction.

[0007] 8NH3+ 3O2→ 4N2+ 6H2+ 6H2O (Formula 2) [Prior art documents] [Patent documents]

[0008] [Patent Document 1] JP 2011-056488 A [Patent Document 2] Patent No. 6566662 [Patent Document 3] Patent No. 6145921 [Patent Document 4] Patent No. 6027467 Summary of the Invention [Problem to be solved by the invention]

[0009] Ammonia reforming catalysts have been studied in the past, but the catalysts used are ruthenium and rhodium, which are rare among precious metals and have many applications such as three-way catalysts for automobile exhaust gas aftertreatment and electrode catalysts for polymer electrolyte fuel cells. There have been significant barriers to expanding the use of ammonia to generate hydrogen for a variety of applications and to making it practical and commercial.

[0010] On the other hand, the ammonia reforming method (Formula 2), in which oxygen is mixed with ammonia gas vaporized from a low temperature when a hydrogen engine or fuel cell is started, and hydrogen is obtained by utilizing the heat generated by the ammonia oxidation reaction, has the advantage of obtaining hydrogen when the hydrogen engine or fuel cell is started, but because ammonia, hydrogen, and oxygen are mixed, the obtained hydrogen reacts with the oxygen, is oxidized, and is consumed as water vapor. 6 moles of hydrogen are obtained from 8 moles of ammonia, and 6 moles of hydrogen are consumed for water vapor, resulting in poor hydrogen generation efficiency.

[0011] The present invention aims to provide an ammonia reforming catalyst that is made of a ruthenium- and rhodium-free catalyst and that uses a composite oxide made of copper and iron, which are base metals that are used in a wide variety of materials and are produced in large quantities, in the direct decomposition of ammonia (Equation 1), with high hydrogen production efficiency from ammonia, high-concentration ammonia reforming processing performance, and high-temperature durability when utilized in solid oxide fuel cells (SOFCs) and hydrogen internal combustion engines that operate at high temperatures of 600 to 1000°C, as well as a method for producing an ammonia reforming catalyst and a method for producing hydrogen gas, thereby making the expansion of a decarbonized, hydrogen-based society a reality.

[0012] In addition, in large internal combustion engines such as ships that use ammonia directly as fuel, the use of hydrogen, which has good ignition properties, as an ignition agent is being considered due to the poor combustibility of ammonia. If hydrogen is extracted from a portion of ammonia using the catalyst of this invention, the combustion efficiency of internal combustion engines that use ammonia as the sole fuel source will be improved, and it will become possible to put into practical use and commercialize power systems with zero CO2 emissions. [Means for solving the problem]

[0013] In order to solve the above problems, the present inventors conducted extensive research and found that a composite oxide having a crystal structure of copper spinel-type CuFe2O4 and / or copper delafossite-type CuFeO2 has activity as an ammonia reforming hydrogen production catalyst.

[0014] Furthermore, they found that a mixture in which the composite oxide coexists with copper oxide CuO(II) exhibits higher catalytic activity.

[0015] The ammonia reforming catalyst of the present invention is an ammonia reforming catalyst for producing hydrogen gas from ammonia gas, and is characterized in that it contains a composite oxide made of copper spinel-type CuFe2O4 and / or copper delafossite-type CuFeO2.

[0016] The ammonia reforming catalyst of the present invention may be a mixture containing the above composite oxide and copper oxide CuO(II).

[0017] The mixture may have a Cu / Fe molar ratio of 0.5 to 1.5.

[0018] The ammonia reforming catalyst of the present invention may be coated on a flow-through substrate having a metallic honeycomb structure.

[0019] At least a portion of the flow-through substrate may include copper spinel CuFe2O4 and / or copper delafossite CuFeO2 adapted to flow ammonia gas therethrough to produce hydrogen gas.

[0020] Furthermore, the hydrogen gas production method of the present invention is a hydrogen gas production method using the ammonia reforming catalyst of the present invention, and is characterized in that oxygen-free ammonia gas is circulated through the portion of the flow-through substrate covered with copper spinel-type CuFe2O4 and / or copper delafossite-type CuFeO2 to generate hydrogen gas.

[0021] The method for producing an ammonia reforming catalyst of the present invention is characterized by comprising the steps of: a) adding an aqueous alkali solution to an aqueous solution of copper nitrate (II) and iron nitrate (III) to obtain a slurry liquid, adjusting the pH to 9 to 11; b) performing solid-liquid separation from the slurry liquid to obtain a solid substance; c) drying and pulverizing the solid substance to obtain a dried product; and d) calcining the dried product in air at 700°C to 1000°C.

[0022] The method for producing an ammonia reforming catalyst of the present invention is characterized by comprising the steps of: a) adding an aqueous solution of copper nitrate (II) and iron nitrate (III) to an inorganic porous catalyst support powder and kneading the mixture; b) drying and pulverizing the kneaded powder to obtain a dried product; and c) calcining the dried product in air at 700°C to 1000°C. Effect of the Invention

[0023] The high activity and durability of the present invention are due to the presence of CuO(II) in the CuFe2O4 composite oxide. In other words, by selective reduction of ammonia, CuO(II) is reduced in the presence of CuFe2O4, and then the Cu-O in the CuFe2O4 component is successively reduced to Cu nanoparticles, and Fe-O becomes Fe3O4, which decomposes into Cu nanoparticles and Fe3O4.

[0024] The interaction between CuFe2O4 and CuO(II) promotes the reduction of Cu nanoparticles in CuFe2O4, and the Cu nanoparticles are uniformly dispersed, achieving high activity at low temperatures. Furthermore, the insolubility of Cu metal particles and Fe3O4 suppresses sintering of Cu particles.

[0025] The present invention has realized that a composite oxide having a copper spinel structure or a copper delafossite structure has catalytic activity for producing hydrogen by reforming ammonia.

[0026] Furthermore, the coexistence of the composite oxide with CuO(II) achieved even higher catalytic activity at lower temperatures. [Brief description of the drawings]

[0027] [Figure 1] 1 shows the results of powder XRD analysis of the composite oxides of copper and iron obtained in Examples 1, 4, and 5. [Diagram 2] Test method for the ammonia reforming hydrogen production catalysts obtained in Examples 1 to 5. [Diagram 3]1 shows the results of evaluation of the performance of the ammonia reforming hydrogen production catalysts obtained in Examples 1 to 5. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0028] Hereinafter, an embodiment of the present invention will be described in detail with reference to the drawings. However, the present invention is not limited to the following embodiment.

[0029] The present invention is characterized in that the components are represented by a mixture of CuFe2O4, CuO(II) and α-Fe2O3, and the composition of the mixture has a Cu / Fe molar ratio of 0.5 to 1.5. The ammonia reforming catalyst of the present invention is an ammonia reforming catalyst for producing hydrogen gas from ammonia gas, and is characterized in that it contains at least a composite oxide having a copper spinel type and / or copper delafossite type crystal structure.

[0030] Furthermore, the ammonia reforming catalyst is characterized in that the composite oxide comprises Cu and Fe or Cu, Ni and Fe.

[0031] In particular, it is preferable that the composite oxide and copper oxide CuO(II) coexist and that the mixture is characterized in that the molar ratio of Cu / Fe is 0.5 to 1.5.

[0032] In addition, from the viewpoint of improving catalytic activity due to the melting point effect, the ammonia reforming catalyst preferably contains 0.5 to 3 mass % of an alkali metal such as Na, K, or Cs.

[0033] As the support substrate for the ammonia reforming catalyst, at least one metal selected from the group consisting of iron, nickel, copper and cobalt and alloys thereof are preferred because they have catalytic activity for ammonia reforming by themselves, and in particular, metal honeycomb substrates made of the above metals and alloys thereof are preferred from the viewpoint of large surface area.

[0034] Next, the synthesis of the ammonia reforming catalyst of the present invention will be described.

[0035] Aspect (1) of the present invention will be described below. Aspect (1) of the present invention is an ammonia reforming catalyst that does not use a catalyst support powder and contains a composite oxide of copper spinel and / or copper delafossite.

[0036] (Copper spinel and / or copper delafossite complex oxide) The copper spinel and / or copper delafossite composite oxide of the present invention is preferably composed of copper and iron.

[0037] First, a method in which the starting materials of the present invention are copper and iron will be described.

[0038] The copper raw material can be an inorganic or organic acid salt such as copper(II) chloride, copper(II) sulfate, copper(II) nitrate, copper(II) phosphate, or copper(II) acetate, with copper(II) nitrate being preferred from the viewpoint of ease of handling during production.

[0039] As the raw material for iron, inorganic or organic acid salts such as iron(III) chloride, iron(III) sulfate, iron(III) nitrate, iron(III) phosphate, and iron(III) acetate can be used. Among these, iron(III) nitrate is preferred from the viewpoint of handling during production.

[0040] Next, the molar ratio of copper to iron will be described.

[0041] It is preferable that a composite oxide of copper spinel and / or copper delafossite is mixed with CuO(II), and the molar ratio of copper to iron, Cu / Fe, is preferably 0.5 to 1.5.

[0042] When the molar ratio of copper to iron, Cu / Fe, is less than 0.5, the amount of CuO(II) decreases, whereas when the molar ratio of copper to iron, Cu / Fe, is more than 1.5, the amount of composite metal oxides, such as copper spinel and / or copper delafossite, decreases.

[0043] Next, a method for synthesizing the ammonia reforming catalyst will be described, although the method is not particularly limited.

[0044] The starting material is added with an aqueous solution of at least one alkali metal selected from Na, K, and Cs to obtain a deep blue gel-like precipitate, which is then filtered, washed with water, dried, and calcined to crystallize the precipitate and obtain an ammonia reforming catalyst.

[0045] First, the above-mentioned method (1) for synthesizing the ammonia reforming catalyst will be described.

[0046] [Method for synthesizing the ammonia reforming catalyst (1)] From the starting materials, for example, copper(II) nitrate trihydrate Cu(NO3)2·3H2O and iron(III) nitrate nonahydrate Fe(NO3)3·9H2O are dissolved in ion-exchanged water with stirring so that the copper to iron molar ratio Cu / Fe is 0.5 to 1.5.

[0047] (Gel formation process) The alkaline aqueous solution is added thereto to adjust the pH, thereby obtaining a deep blue gel-like precipitate.

[0048] The alkaline aqueous solution is preferably an aqueous solution in which a hydroxide or a weak acid salt such as a carbonate of at least one alkali metal selected from Na, K and Cs is dissolved. Ammonia water cannot be used to obtain the mixture of the copper spinel and / or copper delafossite composite oxide of the present invention and CuO(II).

[0049] The copper spinel and / or copper delafossite composite oxide of the present invention and CuO(II) can be stably obtained after firing within the pH adjustment range of pH 9 or more. Therefore, the upper limit of the pH is not particularly limited, but considering the load of wastewater treatment during the subsequent filtration and washing with water, the upper limit may be pH 12.

[0050] On the other hand, if the pH is less than 9, the copper spinel and / or copper delafossite composite oxide of the present invention and CuO(II) cannot be obtained after firing.

[0051] (Post-processing) The gel-like precipitate is filtered and washed with water to obtain a solid product. The filtration and washing method may be a known method, specifically, a reduced pressure method using filter paper and a filter, a pressurized method using a filter press or the like, a solid-liquid separation method using a centrifuge, or a decantation sedimentation method using specific gravity.

[0052] For small-scale production, a reduced pressure method using filter paper and a filter is preferred from the viewpoint of ease in using simple equipment, whereas for large-scale production, a pressurized method using a filter press is preferred from the viewpoint of mass production efficiency.

[0053] (Dry) The drying step of the solid product may be carried out by a known method, and may use a heating dryer in the atmosphere, an air circulation type heating dryer, a vacuum heating dryer, etc. From the viewpoint of drying efficiency, an air circulation type heating dryer or a vacuum heating dryer is preferred.

[0054] The drying conditions are not particularly limited as long as the drying is sufficient, and for example, the drying temperature and time may be set so that the moisture content is less than 1% by mass.

[0055] (Firing) The calcination step of the solid product is preferably carried out for about 1 hour to 6 hours at a temperature in the range of 700° C. to 1000° C. Calcination is preferably carried out so that a composite oxide of copper spinel CuFe2O4 and copper delafossite CuFeO2, and copper oxide CuO(II) are identified by X-ray diffraction analysis.

[0056] (Pre-grinding) Since wet pulverization is performed when preparing a slurry for supporting the catalyst on a metal honeycomb, a preliminary dry pulverization may be performed here. For example, when the amount is small, pulverization may be performed in a mortar. When the amount is large, there is no particular limitation as long as the average particle size D50 can be pulverized to 10 to 100 μm, but a Rotator Beater Mill (manufactured by Lette Co., Ltd.) or an ACM Pulperizer (manufactured by Hosokawa Micron Co., Ltd.) is preferred.

[0057] The embodiment (2) of the present invention will be described below. The embodiment (2) is a method for obtaining an ammonia reforming catalyst by impregnating the surface of an inorganic porous carrier with an aqueous solution of starting materials, and then crystallizing the resulting material by drying and calcining.

[0058] More specifically, aspect (2) of the present invention is characterized in that it contains a catalyst support powder and the ammonia reforming catalyst comprising the copper spinel and / or copper delafossite composite oxide of aspect (1) and CuO(II) is supported on the surface of the catalyst support powder made of an inorganic porous material.

[0059] The embodiment (2) has an advantage in that an ammonia reforming catalyst can be easily obtained by impregnating a porous catalyst support powder with an aqueous solution containing copper and iron, drying and calcining the powder, without using the complicated steps of alkali precipitation and water washing and filtration as in the embodiment (1).

[0060] The copper raw material can be an inorganic or organic acid salt such as copper(II) chloride, copper(II) sulfate, copper(II) nitrate, copper(II) phosphate, or copper(II) acetate, with copper(II) nitrate being preferred from the viewpoint of ease of handling during production.

[0061] As the raw material for iron, inorganic or organic acid salts such as iron(III) chloride, iron(III) sulfate, iron(III) nitrate, iron(III) phosphate, and iron(III) acetate can be used. Among these, iron(III) nitrate is preferred from the viewpoint of handling during production.

[0062] (Catalyst support powder) The catalyst support powder may be a known inorganic porous material, for example, γ-alumina, ceria-zirconia-based oxides, and zeolites such as A-type, chapazite-type, ZSM-5, beta-type, Y-type, and X-type, which are used as support powders for exhaust gas catalysts. Among these, γ-alumina and ceria-zirconia-based oxides are preferred from the viewpoint of heat resistance.

[0063] (specific surface area) The specific surface area of ​​the inorganic porous material of the catalyst support powder is 10 m 2 / g or more is sufficient, and from the viewpoint of increasing the number of catalytic active sites, it is particularly preferable to use a catalyst having a molecular weight of 100m 2 / g or more is more preferable. 2 If it is less than 1 / g, the active sites of the catalyst become too few, which is undesirable.

[0064] The catalyst support powder may have an average particle size distribution of 1 μm to 30 μm, and is particularly preferably 1 μm to 20 μm from the viewpoint of ensuring a path for ammonia gas to penetrate. If the average particle size distribution is less than 1 μm, clogging occurs frequently due to an increase in the viscosity of the coating liquid on the catalyst support substrate described below, which is not preferable.

[0065] In embodiment (2) of the present invention, an ammonia reforming catalyst is produced by impregnating a porous inorganic support with an aqueous solution of copper nitrate (II) and iron nitrate (III), drying the support, and then calcining the support at 700°C to 1000°C in air.

[0066] (Ammonia catalyst support substrate) It will be explained that the ammonia reforming catalysts of the embodiment (1) and embodiment (2) of the present invention are supported on the following support substrate.

[0067] (Metal Honeycomb) The catalyst-supporting substrate is preferably a metal honeycomb made of at least one metal selected from the group consisting of iron, nickel, copper and cobalt, or an alloy thereof, from the viewpoint of enhancing ammonia reforming to generate hydrogen in the above metals and alloys.

[0068] For example, examples of materials that can be used for known metal foils (having a thickness of 20 to 50 μm) include highly oxidation-resistant stainless steels made of iron, chromium, and aluminum (JFE20-5USR or JFE18-3USR, manufactured by JFE Steel Corporation), SUS304 and SUS310 made of iron, chromium, and nickel, and further, SUS303Cu, SUS304J3, SUS316J1, SUS890L, SUSXM7, and SUS630, which contain copper. EXAMPLES

[0069] The present invention will now be described in more detail with reference to examples, but the present invention is not limited to these examples. The tests carried out in the examples were as follows.

[0070] (Measurement method) (1) Powder method X-ray diffraction (XRD) analysis: Using SA-HF3 manufactured by Rigaku, the composite oxides obtained in Examples 1 to 5 were pulverized in an agate mortar and subjected to crystal structure analysis. The measurement conditions were as follows: anticathode: Cu, tube voltage: 40 kV, tube current: 30 mA, full scale (cps): automatically set, scanning speed: 2.0° / min, step width: 0.020°, divergence slit: 2 / 3°, scattering slit: 2 / 3°, receiving slit: 0.3 mm, scanning range (2θ): 20° to 80°.

[0071] (2) Fluorescent X-ray composition analysis: Using a Shimadzu EDX-700HS, the compositions of La in Example 4 and YLaCeZrO8·Al2O3 in Example 5 were analyzed.

[0072] (3) Ammonia gas concentration measurement: Measurement was performed using a DATABIRD FT-IR MOTO EXHAUST GAS ANALYZER.

[0073] (4) Hydrogen gas concentration measurement: Measurements were taken using a gas thermal conduction type high concentration gas detector XP-3140 manufactured by Shin Cosmo Electric.

[0074] (Example 1) Cu / Fe molar ratio is 1.0 20 g of ion-exchanged water was placed in a glass beaker, and 2.8 g of copper(II) nitrate trihydrate, Cu(NO3)2·3H2O (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) and 4.6 g of iron(III) nitrate nonahydrate, Fe(NO3)3·9H2O (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) were added and dissolved while stirring.

[0075] Then, while continuing stirring, a 48% sodium hydroxide solution (Kanto Chemical) was slowly added to adjust the pH to 10.2 to prepare a suspension, which was then aged by keeping it at room temperature for 5 hours so that the reaction in the entire suspension was completed uniformly. The aged suspension was filtered, washed with water, and separated into solid and liquid to obtain a solid product.

[0076] Next, the separated solid product was kept at 80°C for 2 hours, then heated to 120°C and dried for 3 hours, and then calcined in air at 700°C for 2 hours.Furthermore, it was pulverized in an agate mortar to obtain 1.76 g of a solid product.

[0077] The crystal structure of the obtained composite oxide was analyzed by powder X-ray diffraction method, and the results are shown in Example 1 of Figure 1. It was a composite oxide in which CuFe2O4 (JCPDS#77-0010) and CuO (JCPDS#80-1268) were mixed.

[0078] (Example 2) Cu / Fe molar ratio is 1.5 In Example 2, an ammonia reforming catalyst made of a composite oxide was obtained in the same manner as in Example 1, except that the molar ratio of Cu / Fe was adjusted to 1.5.

[0079] 20 g of ion-exchanged water was placed in a glass beaker, and 2.8 g of copper (II) nitrate trihydrate Cu(NO3)2·3H2O (Fujifilm Wako Pure Chemical Industries, Ltd.) and 3.5 g of iron (III) nitrate nonahydrate Fe(NO3)3·9H2O (Fujifilm Wako Pure Chemical Industries, Ltd.) were added and dissolved while stirring.

[0080] Thereafter, while continuing stirring, a 48% sodium hydroxide solution (Kanto Chemical) was slowly added to adjust the pH to 10.2, and the mixture was aged for 5 hours. The solid product was separated from the reaction suspension by filtration and washing with water.

[0081] Next, the separated solid product was kept at 80°C for 2 hours, then heated to 120°C and dried for 3 hours, and then calcined in air at 700°C for 2 hours.Furthermore, it was pulverized in an agate mortar to obtain 1.54 g of a solid product.

[0082] The crystal structure of the obtained composite oxide was analyzed by powder X-ray diffraction method, and it was found to be a composite oxide containing a mixture of CuFe2O4 (JCPDS#77-0010) and CuO (JCPDS#80-1268).

[0083] (Example 3) Cu / Fe molar ratio is 0.5 In Example 3, an ammonia reforming catalyst made of a composite oxide was obtained in the same manner as in Example 1, except that the molar ratio of Cu / Fe was adjusted to 0.5.

[0084] 20 g of ion-exchanged water was placed in a glass beaker, and 2.8 g of copper (II) nitrate trihydrate Cu(NO3)2·3H2O (Fujifilm Wako Pure Chemical Industries, Ltd.) and 9.4 g of iron (III) nitrate nonahydrate Fe(NO3)3·9H2O (Fujifilm Wako Pure Chemical Industries, Ltd.) were added and dissolved while stirring.

[0085] Thereafter, while continuing stirring, a 48% sodium hydroxide solution (Kanto Chemical) was slowly added to adjust the pH to 10.2, and the mixture was aged for 5 hours. The solid product was separated from the reaction suspension by filtration and washing with water.

[0086] Next, the separated solid product was kept at 80°C for 2 hours, then heated to 120°C and dried for 3 hours, and then calcined in air at 700°C for 2 hours.Furthermore, it was pulverized in an agate mortar to obtain 2.71 g of a solid product.

[0087] The crystal structure of the obtained solid product was analyzed by powder X-ray diffraction method, and it was found to be a composite oxide consisting of a mixture of CuFe2O4 (JCPDS#77-0010), α-Fe2O3 (JCPDS#85-0599), and CuO (JCPDS#80-1268).

[0088] (Example 4) Cu / Fe molar ratio 0.5 / 2% La-γ alumina In Example 4, 2% La-γ-alumina was used as a carrier and impregnated with a nitric acid mixture of copper and iron so that the molar ratio of Cu / Fe was 0.5 to obtain an ammonia reforming catalyst made of a composite oxide.

[0089] First, a support made of 2% La-γ-alumina was prepared. 2 Next, 10 g of ion-exchanged water was placed in a beaker, and 0.64 g of lanthanum (III) nitrate hexahydrate La(NO3)3·6H2O (Fujifilm Wako Pure Chemical Industries, Ltd.) was added and stirred to dissolve. The resulting lanthanum nitrate solution was added to the gamma-alumina powder and kneaded so that it was sufficiently impregnated. After that, the powder was dried at 80°C for 2 hours, then heated to 120°C for 3 hours, and then fired at 550°C for 2 hours to obtain 10.2 g of powder. X-ray fluorescence analysis of the powder confirmed that the gamma-alumina powder contained approximately 2% La.

[0090] In the next step, the 2% La-γ-alumina powder was used as a carrier and impregnated with a nitric acid mixture of copper and iron so that the molar ratio of Cu / Fe was 0.5 to prepare a composite oxide.

[0091] Specifically, 20 g of ion-exchanged water was placed in a glass beaker, and 2.8 g of copper (II) nitrate trihydrate Cu(NO3)2·3H2O (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) and 9.4 g of iron (III) nitrate nonahydrate Fe(NO3)3·9H2O (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) were added and dissolved while stirring to obtain a nitric acid solution of copper and iron.

[0092] Next, 3 g of the 2% La-γ-alumina powder obtained in the previous step was weighed out, and the nitric acid solution of copper and iron was added thereto and kneaded so as to be sufficiently impregnated. After that, it was dried at 80°C for 2 hours, then heated to 120°C for 3 hours, and then calcined at 700°C for 2 hours to obtain 5.7 g of a solid product.

[0093] The crystal structure of the obtained solid product was analyzed by powder X-ray diffraction method, and the results are shown in Example 4 of Figure 1. It was a composite oxide containing a mixture of CuFe2O4 (JCPDS#77-0010), α-Fe2O3 (JCPDS#85-0599), and CuO (JCPDS#80-1268).

[0094] (Example 5) Cu / Fe molar ratio 1.0 / YLaCeZrO8·Al2O3 composite oxide In Example 5, a YLaCeZrO8 composite oxide was used as a support and impregnated with a nitric acid mixture of copper and iron such that the molar ratio of Cu / Fe was 1.0 to obtain an ammonia reforming catalyst made of a composite oxide.

[0095] First, a support made of YLaCeZrO8 composite oxide was synthesized. 60 g of ion-exchanged water was weighed into a glass beaker, and while stirring, 2.9 g of cerium (III) acetate monohydrate Ce(CH3COO)3·H2O (Fujifilm Wako Pure Chemical Industries, Ltd.), 5.9 g of zirconium acetate solution (30 mass% as ZrO2, Zircosol ZA-30, Daiichi Kigenso Kogyo Co., Ltd.), 0.33 g of lanthanum (III) acetate monohydrate La(OOCCH3)3·H2O (Fujifilm Wako Pure Chemical Industries, Ltd.), 0.24 g of yttrium (III) acetate tetrahydrate (CH3COO)3Y·4H2O (Fujifilm Wako Pure Chemical Industries, Ltd.), polyethylene glycol 6000, H(OCH2CH2) n 2.8 g of OH (average molecular weight 7300-9300, Fujifilm Wako Pure Chemical Industries, Ltd.) and 8.1 g of Aluminasol AS200 (10 mass% as Al2O3, Nissan Chemical Industries, Ltd.) were added in sequence and thoroughly dissolved. Then, ammonia water (28 mass%, Fujifilm Wako Pure Chemical Industries, Ltd.) was gradually added to adjust the pH to 9.5 and aged for 5 hours. The solid product was separated from the reaction suspension by filtration and washing with water.

[0096] The separated solid product was then kept at 80°C for 2 hours, then heated to 120°C and dried for 3 hours, and then calcined in air at 700°C for 2 hours. It was then crushed in an agate mortar to obtain 4.1 g of a solid product. The crystal structure of the solid product obtained was analyzed by powder X-ray diffraction, and it was found to be a mixture of YLaCeZrO8 composite oxide with a pyrochlore crystal structure and gamma alumina Al2O3.

[0097] The specific surface area of ​​the mixture is 110 m 2 / g, and as a result of fluorescent X-ray analysis, the composition was 51.1 mass% as ZrO2, 24.1 mass% as CeO2, 2.2 mass% as La2O3, 2.1 mass% as Y2O3, and 20.5 mass% as Al2O3.

[0098] In the next step, the YLaCeZrO8·Al2O3 composite oxide powder was used as a support and impregnated with a nitric acid mixture of copper and iron so that the molar ratio of Cu / Fe was 1.0 to prepare a composite oxide.

[0099] Specifically, 20 g of ion-exchanged water was placed in a glass beaker, and 2.8 g of copper (II) nitrate trihydrate Cu(NO3)2·3H2O (Fujifilm Wako Pure Chemical Industries, Ltd.) and 4.6 g of iron (III) nitrate nonahydrate Fe(NO3)3·9H2O (Fujifilm Wako Pure Chemical Industries, Ltd.) were added and dissolved while stirring to obtain a nitric acid solution of copper and iron.

[0100] Next, 3 g of the YLaCeZrO8·Al2O3 composite oxide powder obtained in the previous step was weighed out, and the copper and iron nitric acid solution was added to it and kneaded so that it was sufficiently impregnated. After that, it was dried at 80°C for 2 hours, then heated to 120°C for 3 hours, and then calcined at 700°C for 2 hours to obtain 4.7 g of a solid product.

[0101] The crystal structure of the obtained solid product was analyzed by powder X-ray diffraction method, and the results are shown in Example 5 in Figure 1. It was a composite oxide of CuFe2O4 (JCPDS#77-0010) and CuO (JCPDS#80-1268).

[0102] (Preparation of catalyst coating slurry) 20 g of alumina balls (outer diameter 5 mm) and 20 g of ion-exchanged water were weighed into a 100 ml polyethylene container, and 4 g of the composite oxide of Examples 1 to 5, 4 g of Alumina Sol AS200 (10 mass% as Al2O3, manufactured by Nissan Chemical Industry Co., Ltd.), and 0.1 g of cesium nitrate CsNO3 (manufactured by Fuji Film Wako Pure Chemical Industries, Ltd.) were added thereto, and the mixture was used in a ball mill to adjust the average particle size D50 to 10 to 20 μm using a laser diffraction particle size distribution measuring device, thereby producing a catalyst coating slurry liquid.

[0103] (Metal honeycomb catalyst support method) Using a metal honeycomb (outer diameter 20 mm × length 10 mm, cell number 300 cpsi) made of metal foil (JFE20-5USR, thickness 30 μm, manufactured by JFE Steel), a catalyst coating slurry liquid made of the composite oxides of Examples 1 to 5 was repeatedly applied to the metal honeycomb at a volume of 100 g / L per space of the metal honeycomb, and the catalyst was supported by drying with a dryer and firing at 550°C for 2 hours.

[0104] (Test method for hydrogen production performance by ammonia reforming) The metal honeycomb carrying the catalyst of Examples 1 to 5 was tested for its ammonia reforming hydrogen production performance as follows. As shown in Fig. 2 as a test system, the metal honeycomb (catalyst-carrying metal honeycomb 10) was wrapped with isowool (gas sealing wool 11) (manufactured by Isolite Industries) around its outer periphery to prevent ammonia gas from flowing, packed into the center of a quartz glass tube 20, and further placed in the center of a tubular heating furnace 40.

[0105] The test gas conditions were a space velocity of 25,000 h -1 The electric furnace temperature was adjusted between 350°C and 700°C in 50°C increments, the honeycomb inlet temperature was measured with a thermocouple (temperature detection thermocouple 30), the ammonia concentration was adjusted to 4 volume% with FT-IR, and the balance gas was N2. The hydrogen gas generated was detected with a gas thermoelectric high concentration gas detector (hydrogen concentration detector 50) (XP-3140, manufactured by Shin Cosmo Electric). Figure 3 shows the results of hydrogen gas generation. Table 1 also shows the Cu / Fe molar ratio, the composition of the catalyst components, and the presence or absence of carrier powder and its composition for Examples 1 to 5.

[0106] [Table 1]

[0107] 3, as described above, in Examples 1 to 5, the ammonia reforming catalysts that generate hydrogen from 4% ammonia gas generated 7% hydrogen by 600° C., and high hydrogen generation efficiency was obtained. In particular, Examples 1 and 2, which had a Cu / Fe molar ratio of 1 to 1.5 and did not use a porous support powder, had high hydrogen generation efficiency. [Industrial Applicability]

[0108] The ammonia reforming catalyst of the present invention is a mixture of a composite oxide containing at least a crystal of copper spinel type CuFe2O4 and / or copper delafossite type CuFeO2 as a composite oxide consisting of base metal copper and iron, which are used in a wide variety of materials and are used in large quantities, and CuO(II), and the molar ratio of copper to iron in the mixture is 0.5 to 1.5. Compared with ammonia reforming catalysts consisting of conventional precious metals (e.g., ruthenium or rhodium), the catalyst has abundant metal resources, can reduce costs, has high hydrogen production efficiency by direct decomposition reaction from high concentration ammonia, and has good high-temperature heat resistance, so that it is useful for industrial use in fuel cells and hydrogen internal combustion engines, and can be put into practical use and commercialized, and is expected to greatly contribute to the development of a decarbonized and hydrogen-based society as a measure against global warming. [Explanation of symbols]

[0109] 10: catalyst-supported metal honeycomb, 11: gas sealing wool, 20: quartz glass tube, 30: temperature detection thermocouple (catalyst inlet), 31: temperature detection thermocouple (catalyst outlet), 40: tubular heating furnace, 50: hydrogen concentration detector, L1: ammonia gas, L2: hydrogen generation gas

Claims

1. In an ammonia reforming catalyst for producing hydrogen gas from ammonia gas, Copper spinel CuFe 2 O 4 and / or copper delafossite type CuFeO 2 1. An ammonia reforming catalyst comprising a composite oxide comprising:

2. 2. The ammonia reforming catalyst according to claim 1, which is a mixture containing the composite oxide and copper oxide CuO(II).

3. 3. The ammonia reforming catalyst according to claim 2, wherein the mixture has a Cu / Fe molar ratio of 0.5 to 1.

5.

4. 2. The ammonia reforming catalyst according to claim 1, characterized in that it is coated on a flow-through substrate having a metallic honeycomb structure.

5. At least a portion of the flow-through substrate is a copper spinel CuFe 2000 adapted to pass ammonia gas through it to generate hydrogen gas. 2 O 4 and / or copper delafossite type CuFeO 2 5. The ammonia reforming catalyst of claim 4, comprising:

6. A method for producing hydrogen gas using the ammonia reforming catalyst according to claim 5, The flow-through substrate copper spinel type CuFe 2 O 4 and / or copper delafossite type CuFeO 2 A method for producing hydrogen gas, comprising the steps of: passing oxygen-free ammonia gas through a portion covered with the catalyst; and generating hydrogen gas.

7. A method for producing the ammonia reforming catalyst according to claim 1, comprising the steps of: a) adding an alkaline aqueous solution to an aqueous solution of copper (II) nitrate and iron (III) nitrate to adjust the pH to 9 to 11 to obtain a slurry liquid; b) performing solid-liquid separation from the slurry liquid to obtain a solid material; c) drying and pulverizing the solid material to obtain a dry material; d) calcining the dried product in air at 700°C to 1000°C; A method for producing an ammonia reforming catalyst, comprising:

8. A method for producing the ammonia reforming catalyst according to claim 1, comprising the steps of: a) adding an aqueous solution of copper (II) nitrate and iron (III) nitrate to an inorganic porous catalyst support powder and kneading the mixture; b) drying and pulverizing the kneaded powder to obtain a dry product; c) calcining the dried product in air at 700°C to 1000°C; A method for producing an ammonia reforming catalyst, comprising:

Citation Information

Patent Citations

  • Method for deciding end point of internal refractory lining material of vessel for molten metal

    JP1985027467A

  • Azimuth detecting device for vehicle

    JP1986045921A

  • Ammonia reforming catalyst and method of manufacturing hydrogen using the same

    JP2011056488A

  • Ammonia oxidative decomposition catalyst, and hydrogen production method and hydrogen production device using the ammonia oxidative decomposition catalyst

    JP6566662B2